PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP LEARNING ORGANIZATION PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA HUKUM DAN HAM KEMENTERIAN HUKUM DAN HAM RI - Lita Regiana (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. Substitution of leader that causes changes in leadership style, thepresence of factors inhibiting the work culture of discipline and ability to adaptand percentage of employees who participate in training are problems that canhinder learning organization. This study aimed to examine the effect of leadershipstyles, organizational culture and emotional intelligence toward learningorganization in the Human Resources Development Agency of Law and HumanRights, Ministry of Law and Human Rights. This study used quantitative methods.The population of this study is all the employees of the Agency as many as 175people. The sampling technique using probability sampling, with proportionalrandom sampling, found a sample of 122 people, obtained by the formula Slovin.Data were analyzed using multiple regression analysis. The results showed thatthe leadership style, organizational culture and emotional intelligence partiallyand simultaneously have significant effect on learning organization.Transformational leadership style, learning culture and social skills have a moresignificant effect than the other dimensions to the dimensions of a learningorganization. Transformational leaders, the formation of a culture of learning andthe improvement of adaptability skills can promote the establishment of a learningorganization.Keywords: leadership style, organizational culture, emotional intelligencelearning organization.